ANALISIS KOMPETENSI KEWIRAUSAHAAN SISWA SEKOLAH MENENGAH KEGURUAN NEGERI VI MAKASSAR - Yusrab Ardianto Sabban (Jurnal Bisnis dan Kewirausahaan, 2019)
There are several things why Makassar State Vocational High School 6 students are not interested in entrepreneurship after graduation, including not taking risks, fear of failure, lack of capital and preferring to work as kryawan in other people. As a result, individuals think that entrepreneurship is something that is difficult to do and is more fun to work for companies or other people.This study aims to determine the entrepreneurial competency characteristics of Makassar State Vocational High School 6 students to be able to carry out entrepreneurial activities. Data collection is done through questionnaires. For the determination of respondents in this study conducted randomly. While determining the sample size of the population using Slovin formula. The analytical tool used is descriptive analysis using tables and Likert scales.The results of the analysis show that the entrepreneurial competency characteristics of the SMK Negeri 6 Makassar students are in the positive category, seeing the total weight of the indicators is 7733 according to the interpretation of scores in Median-Quartiles III or 6000-8000.